ESTIMATION OF TRAIN CHARACTERISTICS USING DATA FROM EXPERIMENTAL JOURNEYS (Ta'limning zamonaviy transformatsiyasi, 2024)
This article exposition delves into the pivotal task of discerning fundamental train parameters through the scrutiny of data acquired from experimental journeys. The investigation delves into the importance of precisely ascertaining these parameters for the optimal functionality and safety of railway systems. By means of an exhaustive literature review, the article aspires to ascertain the present state of knowledge within this domain, pinpointing lacunae that necessitate further investigation. Following this, the research methodology meticulously outlines the approach employed to extract and analyze pertinent data from experimental trips. The section on analysis and results elucidates insights derived from empirical findings, providing illumination on the identification of pivotal train parameters. Finally, the conclusion succinctly encapsulates the contributions of the study and suggests potential avenues for future research endeavors aimed at advancing processes related to the identification of experimental trips.